Brief notes on the control of conventionality: a new paradigm for the Brazilian judiciary (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This study focuses on the dialog between Courts with a special emphasis on the interpretative activity of the law enforcer. It addresses the hermeneutics of constitutional law. It analyzes the citizen as the ultimate interpreter of the Constitution, and the hermeneutic-concretizing method as the shaper of a constitutional legal system that is open and integrated with the social reality it aims to regulate. It shows that constitutional pluralism requires the constitutional interpreter to engage in a dialog between Courts. The topic dealt with is of great importance because the universal claim to human rights protection is the main theoretical foundation for the practice of transnational dialogue, together with the differentiated status of human rights treaties and the similarity between the object of protection of human rights norms and the protective norms of domestic law. Thus, we have a system with multiple levels of protection, in which the maxim of the primacy of the rule most favorable to the victims applies. Furthermore, the interpreter's argumentative activity during constitutional interpretation has the power to achieve effective legal-discursive integration.
Keywords: Constitutional Law; International Law; constitutional pluralism; International Courts; Control of Conventionality